FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT PADA GURU PENDIDIK ANAK BERKEBUTUHAN KHUSUS (ABK) DI SLB NEGERI DI KOTA DENPASAR - Warmaningsih, Ni Made Winda; Puspita, Luh Mira; Damayanti S, Made Rini (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024DO - 10.24843/coping.2024.v12.i04.p04, 2025)
Education is very crucial for every human to improve their quality of life, without exception for Children with Special Needs. In the implementation of special education, teacher is one of important factors in childrens’s learning process. Its is common for teachers who deal with special needs children to experience stress due to the effect of the children’s attitude and as result long lasting stress will cause fatique for the teachers. Thissstudy aimedttooanalyzeetheffactorsaassociated withhburnout toward teachers for special needs children. Thissresearch applied descriptive-correlationalddesignwwithccross-sectionalaapproach. Theesample of thissstudy was 43 teachers who met the inclusion and exclusion criteria with a total sampling research technique. MBI questionnaire was administrated as data collection tool to measure the level of burnout. Bivariate analysis used the spearman test for data on age, last education, years of service, employment status, and the eta test for gender and marital status data with a 95% confidence level (?=0.05). The results showed relationship between no burnout (p=0.841), gender with burnout (p=0.361), last education with burnout (p=0.542), marital status with burnout (p=0.288), lengthhof service with burnoutt (p=0.470), employment status with burnoutt (p=0.278), and income with burnout (p = 0.904). Burnout score level on ABK teachers is 5, meaning that teachers need to monitor the situation at hand so that the burnout experienced does not become high. Basedoontthe resultssoffthissstudy, itiisssuggestedttotthe authorities to make counseling for teachers who indicated stress, so it is able to minimize high burnout.